Congenital cervical rib causing thoracic outlet syndrome - Thomas Heye; Mary Roz Timbang; Lawrence Greiten; Gresham Richter (Elsevier, 2022)
Background: Thoracic Outlet Syndrome (TOS) is a common condition caused by compression of neurovascular vessels traveling through the thoracic outlet. There are three categories of TOS, arterial (aTOS), neurogenic (nTOS), and venous (vTOS). These commonly present with pain in the neck, upper extremity weakness, paresthesia, swelling, and discoloration. TOS can be caused by a cervical rib, which is a rare and usually benign anomaly. This typically results in aTOS. Case: This case, however, presents a 13-year-old male patient with nTOS caused by a cervical rib. He presented with weakness and pain of his right arm and a prior history of a partial neck mass resection. A physical exam revealed a firm supraclavicular mass and X-ray images confirmed the diagnosis of nTOS. Surgical resection of the anomalous rib was performed via a supraclavicular approach. Due to the difficulty of this operation, a multidisciplinary surgery team was formed, ensuring a positive outcome for the patient. Conclusions: To our knowledge only two case reports of nTOS caused by a cervical rib compression of the brachial plexus exist. One was iatrogenic and the other treated non-surgically. Due to this lack of knowledge as well as the debate on surgical versus non-surgical treatment of TOS, this case report seeks to bolster the current literature with a positive outcome to correction of a rare presentation.